Review of the neglected tropical diseases programme implementation during 2012-2019 in the WHO-Eastern Mediterranean Region - Supriya Warusavithana; Hoda Atta; Mona Osman; Yvan Hutin (Public Library of Science (PLoS), 2022)
Introduction The 2012-2020 WHO NTD roadmap set targets for control, elimination, and eradication of neglected tropical diseases (NTDs). It recommends 5 strategies, out of which preventive chemotherapy (PC) and intensified disease management were key to achieve targets. WHO estimated that globally, between 2012 and 2019, the number of persons affected by NTDs decreased from nearly 2.1 to 1.7 billion people. We analysed the situation of NTDs in the WHO Eastern Mediterranean Region (EMR) in 2020 to assess the progress with the 2012-2020 roadmap and to identify gaps. Methods We reviewed data repositories of national data sources for 2012 to 2019 including the Global Indicator Data Platform for Sustainable Development Goals, the Global Health Observatory data repository, the WHO PC databank, and the EMR data repository. We allocated countries a Red-Amber-Green (RAG) rating based on standardized criteria, on progress and current situation of each of 11 priority NTDs. Results All 22 countries in EMR were affected by 1 or more autochthonous or imported NTDs. In 2019, WHO estimated that in EMR, 78 million people required interventions for NTDs, a 38% decline compared with 2012. Twelve of 22 countries needed priority public health action (i.e., red) for 1 or more NTD. Of these, Sudan needed priority public health action for 6 NTDs and Yemen for 5. Eleven countries also needed priority public health action for cutaneous leishmaniasis, and 5 countries for rabies and trachoma. Visceral leishmaniasis is on the increase in Afghanistan, Libya, Syria, and Yemen. Conclusion Since the first roadmap of NTDs in 2012, the EMR has made a substantial progress. Nevertheless, many challenges remain in the prevention and control of NTDs. EMR needs a regional approach to control NTDs in countries most affected and a coordinated strategy to stop the continuing increase of cutaneous leishmaniasis and a possible resurgence of visceral leishmaniasis.